Legal Status of Social Inquiry Reports in Juvenile Sentencing under the Best Interests of the Child Principle - Furkon Adi Hermawan; Abdul Madjid; Patricia Audrey Ruslijanto (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
Juvenile sentencing is designed to reflect the principles of protection, rehabilitation, and the best interests of the child. In Indonesia, Law Number 11 of 2012 on the Juvenile Criminal Justice System requires judges to consider Social Inquiry Reports (Laporan Penelitian Kemasyarakatan or Litmas) prior to imposing sentences on children. This article examines the legal status of Social Inquiry Reports and clarifies the normative meaning of the obligation to consider them within judicial reasoning. Using normative legal research with statutory, conceptual, and case approaches, the study analyzes relevant legislation, legal doctrines, and selected juvenile court decisions. The findings indicate that Social Inquiry Reports function as non-juridical instruments intended to support individualized sentencing rather than as binding recommendations. Judicial practice, however, demonstrates varying degrees of engagement with these reports, ranging from formal reference to substantive consideration. This article concludes that interpreting the obligation to consider Social Inquiry Reports as a substantive and argumentative duty enhances the application of the best interests of the child principle while preserving judicial independence in juvenile sentencing. By framing Article 60(3) as a reason-giving duty, this article offers an operational standard for assessing whether judges meaningfully engage with Litmas in their sentencing reasons, thereby enriching the discussion on individualized juvenile sentencing.